Reasons for leaving the clerical state marital adjustment, problems and coping strategies of Catholic married priests in the Philippines - Janetius, Servasious Thomas (Animo Repository, 1997)
This study creates a profile of Catholic married priests in the Philippines with special reference to: the age, educational qualification, number of years in the active ministry, reasons for leaving, initial problems, coping strategies used to overcome the problems and their present level of marital adjustment. Two questionnaires were used in this exploratory-descriptive study: (a) survey questionnaire (b) marital adjustment questionnaire. By convenient sampling, the data was collected from 52 Catholic married priests all over the Philippines. The age range was 43-74.The findings revealed that the priests left the clerical state in mid-life and their mean age was 39. Majority of them left because of falling in love. Doctrinal differences, misunderstanding with the superiors were the other significant reasons. Three fourths of the married priests were seminary graduates. Getting a job was their major problem. Financial difficulties, criticism from the people, marital adjustment and ashamed to face the people were the other continuing problems. Dependence on God was their top coping strategy. They were more or less settled in life after four years of married life. Their present level of marital adjustment is good. This study contradicted few common beliefs regarding married priests, namely, those who join the seminary at an early age, fall in love and leave priest who neglect prayer life leave and those who have no vocation leave. This study concluded further that priests are vulnerable at mid-life and a serious decision making is done at this period of adult development irrespective of their previous commitment to be a life long celibate minister. It is not the priesthood but celibacy which is understood as the cause of priests leaving the ministry. Majority of them desire to be married priests if the Church allows them to be so. Many years of single celibate life had no negative effect on their marital life. Periodical courses on adult development at mid-life were suggested to help priests and celibate aspirants. Moreover, vocation to priesthood and life of celibacy are of two different nature and the possibility of reintroducing the optional celibacy was recommended. Since change and decision-making are possible at different stages of adult development, renewable commitment for 3 or 5 years is seen as more realistic than life long commitments.